Two Identity Builders in Amity and Enmity: Religion and Politics - Kundukulam, Vincent (Journal of Dharma, 2015)
Religion and politics are the two ancient social institutions which propose, each in its own way, a notion of how to live in this world. Since both of them structure the social living of people they are everywhere interactive. The constant interaction of politics and religion in different countries gives birth to diverse forms of political and religious co-habitations and there emerges consequent issues revolving their identities, methods of reaching out to people and means of their survival. This paper explains the rationale of the inevitable alliance between politics and religion, exposes the important models of politics and religion co-existing in the current world and examines the potential of religion to withstand the attempts of politics to overwhelm religion. It also envisages that the emerging cold war between secular and religious nationalisms will not result in disastrous casualties.